An approximate method to find changes in the blood flow characteristics in a larger coronary artery due to the appearance of its pathological tortuosity. Clinical application - Borysyuk, A. O.; Sebov, D.M. (Reports of the National Academy of Sciences of Ukraine, 2023)
An approximate method was developed to enable cardiologists to determine (with acceptable precision and speed) both quantitative changes in the blood flow characteristics of interest in larger coronary arteries, caused by the appearance of their pathological tortuosity, and a hemodynamic significance of those changes based on the data taken from the appropriate coronarographies only. The method was successfully tested in-vitro, after that (proceed from the results of this test) recommended by cardiologists for use in clinical applications. This use re- vealed that the hemodynamic significance of the tortuosity generally increases/decreases as the number of the tortuosity arcs increases/decreases. Also, strong correlation between fundamental geometric and hemodynamic characteristics of the tortuosity and basic clinical indicators of the corresponding patients was established. This suggests a strong independent influence of the pathological tortuosity of larger coronary arteries on the clinical symptoms of the corresponding patients. Another important result of the clinical application of the method is that the critical values for the number of the tortuosity arcs, the relative blood flow rate loss and the rate of an- gina pectoris attacks were obtained, starting from which the corresponding tortuosity can be hemodynamically significant. The results obtained in the framework of the method and their analysis established a basis for a future successful clinical application of the method.